A Subtitling Analysis Of English Modal Verbs In Percy Jackson: Sea Of Monsters And Subtitling - PANGESTU, PANGGIH, Dr. Dwi Haryanti, M.Hum, Siti Fatimah, S.Pd. M.Hum (2015)
The research paper studies about English modal verb in subtitling Percy Jackson: Sea of Monsters movie script. The study aims (1) to identify subtitling variations using of the English modal verbs in Percy Jackson: Sea of Monsters movie and subtitling and (2) to describe the accuracy of English modal verbs translated into Indonesian and its subtitling in Percy Jackson: Sea of Monsters movie and subtitling. The type of this research is descriptive qualitative research. The object of the study is the movie entitled Percy Jackson: Sea of Monsters and its subtitling. The data of this study is sentences consisting modal verb found in Percy Jackson: Sea of Monsters movie script. Data source used in this research are the documentation of the data research paper and the raters. The researcher uses document, questionnaire, and interview raters in collecting data. The data are analyzed by using comparing method. The result of the study shows that there are 4 types of English modal verb. 64 data or 40% English modal verb translated into modal verb, the English modal verb translated into Indonesian modal verb can be divided into six, such as: 25 data or 39.1% will, 11 data or 17.2% would, 5 data or 7.8% could, 12 data or 18,7% can, 3 data or 4.7% might, 8 data or 12.5% have to. 32 data or 20% English modal verb translated into adverb, the English modal verb translated into adverb can be divided into seven, such as: 2 data or 6.3% will, 2 data or 6.3% would, 4 data or 12.5% could, 4 data or 12.5% can, 10 data or 31.2% may, 2 data or 6.2% might, 8 data or 25% should. 53 data or 33.1% English modal verb translated into verb, the English modal verb translated into verb can be divided into nine, such as: 9 data or 17% will, 3 data or 5.7% would, 5 data or 9.4% could, 15 data or 28.3% can, 1 data or 1.9% might, 6 data or 11.3% should, 4 data or 7.5% have to, 7 data or 13.2% shall, 3 data or 5.7% must. 11 data or 6.9% English modal verb is omitted or deleted, the English modal verb is omitted or deleted that can be divided into six, such as: 2 data or 18.2% will, 4 data or 36.4% would, 1 data or 9.1% could, 2 data or 18.2% might, 1 data or 9.1% may, 1 data or 9.1% have to. The accuracy of the data shows that rater gets 3 score 145 data or 90.6%, 12 data or 7.5% get 2 score, and the less 3 data or 1.9% get 1 score.